Comparison of protein expression between human livers and the hepatic cell lines HepG2, Hep3B, and Huh7 using SWATH and MRM-HR proteomics: Focusing on drug-metabolizing enzymes - Shi, Jian; Wang, Xinwen; Lyu, Lingyun; Jiang, Hui; Zhu, Hao-Jie (Drug metabolism and pharmacokinetics, 2018)
Human hepatic cell lines are widely used as an in vitro model for the study of drug metabolism and liver toxicity. However, the validity of this model is still a subject of debate because the expressions of various proteins in the cell lines, including drug-metabolizing enzymes (DMEs), can differ significantly from those in human livers. In the present study, we first conducted an untargeted proteomics analysis of the microsomes of the cell lines HepG2, Hep3B, and Huh7, and compared them to human livers using a sequential window acquisition of all theoretical mass spectra (SWATH) method. Furthermore, high-resolution multiple reaction monitoring (MRM-HR), a targeted proteomic approach, was utilized to compare the expressions of pre-selected DMEs between human livers and the cell lines. In general, the SWATH quantifications were in good agreement with the MRM-HR analysis. Over 3000 protein groups were quantified in the cells and human livers, and the proteome profiles of human livers significantly differed from the cell lines. Among the 101 DMEs quantified with MRM-HR, most were expressed at substantially lower levels in the cell lines. Thus, appropriate caution must be exercised when using these cell lines for the study of hepatic drug metabolism and toxicity. [Display omitted]